Prevalence and type distribution of human papillomavirus in a Chinese urban population between 2019 and 2023: a retrospective study - Xu, Mei-Yan; Feng, Mei-Jing; Geng, Wen-Yao; Liu, Xue-Kai; Ma, Rui (Frontiers in Microbiology, 2026)
IntroductionHuman papillomavirus (HPV) infection is one of the most common sexually transmitted infections among women worldwide. The present study reports the prevalence and type distribution of HPV in the same hospital between 2019 and 2023, and analyzes the impact of the COVID-19 pandemic on HPV infection.MethodsFemale participants aged ≥18 years old were recruited from Aerospace Center Hospital in Beijing, China, between 2019 and 2023. A total of 27 HPV types were detected using fluorescence quantitative polymerase chain reaction.Results37,225 women underwent at least one HPV test, with an overall positive rate of 10.22%. The HPV positive rates in the age groups of ≤45 years, 46–60 years, and >60 years were 9.44, 11.61, and 11.14%, respectively. By year, the positive rates were 5.19% in 2019, 11.60% between 2020 and 2022, and 9.37% in 2023. Women with uterine fibroids or a history of hysterectomy/ovariohysterectomy had higher HPV positive rates than those without these conditions. Compared with the pre- and post-COVID-19 periods, the HPV positive rate was significantly higher during the pandemic (2020–2022). Among high-risk HPV types, the top five most prevalent ones (by positive case count) were HPV52, 16, 58, 53, and 56. For low-risk HPV, HPV61 had the highest positive rate from 2020 to 2023. Single-type HPV infection accounted for the highest proportion across all age groups and years. Joinpoint regression analysis showed that the HPV positive rate decreased sharply in the 31–35 years age group (Annual Percent Change [APC] = −22.2%, 95% Confidence Interval [CI] = −27.9 ~ −13.1), then increased steadily until the 66–70 years age group (APC = 6.9%, 95% CI = 5.5 ~ 8.3), and declined again thereafter (APC = −18%, 95% CI = −25.4 ~ −7.3).DiscussionThere may be a potential association between the COVID-19 pandemic and HPV transmission. Our findings provide valuable insights for optimizing HPV screening strategies and formulating HPV prevention measures. The association between gynecological diseases and specific HPV types requires further investigation.